Uso de aplicativo no ensino de química: entrelaces de representações imagéticas a partir da perspectiva vigotskiana - Jesus, Chelry Fernanda Alves de (2020)
This work aimed to discuss the usage of an application (App) in Chemistry classes when the content state of matter was taught. The research theme came out due to the teaching-learning process supported by digital information and communication technologies – ICTs and contextualized the possibilities a smartphone may offer, as well as the issues involved in the insertion of these resources , in classes, as pedagogical tools. Thus, the research aimed to understand how the development of scientific concepts mediated by signs and the App, based on the theory by Lev Vygotsky, such as the development of concepts, semiotics mediation and generalizations. The research was conducted with a high school class of a Basic Education school based in Aparecida de Goiânia, a municipality belonging to the metropolitan region of Goiânia, the state capital of Goiás, with the participation of XX students. The applied nature and qualitative approach study used action research as a methodological path, in which the researcher placed herself in the roles of professor and researcher at the same time, and could focus on the analysis of her own actions. Results indicated that the students bring concepts of a spontaneous nature regarding the content addressed, in which they related the substance water and its characteristics to the physical states of matter. During the classes, the use of the application helped in the process of developing the concepts, while put in evidence the interaction of the students and the application, which, on its turn, consists of visual representations. That is, they are mediating signs of the process of signification of concepts in the mental plane. In this regard, visualization of these imagery representations of the application during the course of the lesson proved to be an important semiotic tool that gained meaning through the word in thought. However, the data analysis indicated that the development of scientific concepts occurred in a timid way, and at the end of the process it still showed some relevance of spontaneous concepts. This fact put in evidence other aspects which influenced the scientific concepts development process during classes, such as the relationship of the subject with the knowledge that was discussed from the perspective of the teacher, and unveilled issues that permeate this discussion such as the formation of Chemistry teachers and the conception of Science